(untitled) ("Temas Sociais" Journal, 2023)
Addictive behaviors and dependencies are complex issues that requires multidisciplinary efforts for concerted intervention, both from a professional and political perspective. Political investment is seen, in Portugal, in the creation and implementation of articulated responses between health and social action, through the Intervention Service for Addictive Behaviors and Dependencies. Based on a critical review of the literature, we outlined Portuguese policy on addictive behaviors and the social intervention carried out in this context. In social intervention, social workers play an important role in prevention, treatment, social reintegration and harm reduction. The role of the social worker in the different areas of intervention is highlighted, emphasizing systemic and ecological models. In the construction of the theoretical body intended for Social Work, is essential to invest in research that, in this way, contributes to a robust and specialized theoretical-practical intervention.